Manifestations of dating violence among college students: an integrative review - Guerrero Ramírez, Adriana María (2021)
Aim: Identify the manifestations of dating violence in university students. Methods: It consisted of an integrative review that arose from the research question: What are the manifestations presented by university students that suffer from dating violence? The research strategy was carried out during the first semester of 2020 using databases such as EBSCO, Science direct, ProQuest, Lilacs, CUHSO, and the scientific journal Scielo; the reviewed literature included qualitative and quantitative studies in either English or Spanish that studied university students between 18 and 26 years old. The exclusion criteria to not consider other articles were the lack of accessibility criteria or incompleteness of the texts. Finally, 51 articles were found; 42 of them were excluded, and the remaining 9 were included in the final analysis. The documents were analyzed using a constant comparison method. Results: The manifestations of dating violence are complex since there are several ways in which they can manifest: from psychological aspects (such as behavior, attitude, emotions, and self concept), to social, physical, sexual, and academic aspects. Conclusion: The manifestations of dating violence are diverse and can be detected by nursing professionals in the various dimensions of the individuals involved in this phenomenon.